The The Correlation between Parenting and Stunting in Pematang Reba Subdistrict, in the Working Area of the Pekan Heran Public Health Center, Indragiri Hulu Regency - Alice Rosy; Yulianto Yulianto (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2022)
Stunting is a condition of failure of growth in children caused by chronic malnutrition, especially in the first 1000 days of life so that the child is too short for their age, the condition of stunting only appears after the child is 2 years old. Stunting occurs due to chronic malnutrition caused by poverty and improper parenting, resulting in underdeveloped cognitive abilities, prone to illness, and low competitiveness so that they can be trapped in poverty. Several factors are related to the case of stunting, such as parental characteristics, namely education, employment, income and parenting manners. This research is a quantitative study with a cross sectional approach, with a total sample of 70 people. This study aims to determine the relationship between maternal parenting and the case of stunting in children in the working area of Pekan Heran Public Health Center, Rengat Barat District, Indragiri Hulu Regency. Based on the statistical test, the results of the study showed that there was a significant relationship between the case of stunting and parenting with a p value of 0.003, and of the 70 respondents, the largest proportion of parenting was democratic parenting as many as 46 respondents (75.7%), and there were 11 stunted children (15.7%).